Legal Protection of Processed “Nasi Kapau” Products are Linked to Intellectual Property Rights (Study at Nagari Kapau, Agam Regency) - Ulfanora Utama; Tasman (Dinasti Research, 2024)
West Sumatra is a province that has undoubted delicious cuisine that has gone global and is known as Minangkabau cuisine. One of the famous Minangkabau dishes is Nasi Kapau. Nasi Kapau is a traditional dish originating from Nagari Kapau and has special processed products that are different from dishes in the Minangkabau realm. In Law Number 20 of 2016 concerning Brands, the role of Brands and Geographical Indications is very important, especially in maintaining healthy, fair business competition, protecting consumers, as well as protecting Micro, Small and Medium Enterprises and domestic industry. In fact, there are already several Nasi Kapau dishes that have been registered with the Ministry of Law and Human Rights, such as Nasi Kapau Uni Lis. The potential for not carrying out an inventory or recording it will give rise to legal problems, namely legal disputes. Various cases that have occurred bothclaim